Salmonella and Campylobacter biofilm formation: a comparative assessment from farm to fork. (14th March 2018) - Lamas, Alexandre; Regal, Patricia; Vázquez, Beatriz; Miranda, José M; Cepeda, Alberto; Franco, Carlos M
Abstract: It takes several steps to bring food from the farm to the fork (dining table), and contamination with food‐borne pathogens can occur at any point in the process. Campylobacter spp. and Salmonella spp. are the main microorganisms responsible for foodborne disease in the EU. These two pathogens are able to persist throughout the food supply chain thanks to their ability to form biofilms. Owing to the high prevalence of Salmonella and especially of Campylobacter in the food supply chain and the huge efforts of food authorities to reduce these levels, it is of great importance to fully understand their mechanisms of persistence. Diverse studies have evaluated the biofilm‐forming capacity of foodborne pathogens isolated at different steps of food production. Nonetheless, the principal obstacle of these studies is to reproduce the real conditions that microorganisms encounter in the food supply chain. While there are a wide number of Salmonella biofilm studies, information on Campylobacter biofilms is still limited. A comparison between the two microorganisms could help to develop new research in the field of Campylobacter biofilms. Therefore, this review evaluates relevant work in the field of Salmonella and Campylobacter biofilms and the applicability of the data obtained from these studies to real working conditions. © 2018 Society of Chemical Industry